Subcutaneous nephrovesical bypass: Treatment for ureteral obstruction in advanced metastatic disease - WANG, YUNYAN (Oncol Lett, 2015)
The aim of the present study was to explore the value of subcutaneous nephrovesical bypass (SNVB) for the treatment of ureteral obstruction due to pelvic metastatic disease. SNVB stents (n=30) were implanted in 24 patients with advanced metastatic disease between January 2008 and December 2012. Urinalysis, serum creatinine (SCr), glomerular filtration rate (GFR), quality of life (QoL) scores, and renal ultrasonography were evaluated at follow-up. The SNVB procedures were successful in all 24 patients. Patient follow-ups occurred at an average of 10.6 months. Preoperative hydronephrosis was eliminated in 16 cases (53.3%) and reduced in the remaining patients. Following surgery, SCr levels reduced significantly from 256±46 to 124±23 μmol/l (P<0.001). GFRs increased from 25±4.8 to 45±5.3 ml/min (P<0.01). The mean QoL scores were 3.4±1.4 preoperatively and 7.6±1.0 postoperatively (P<0.001). The results showed that SNVB is a minimally invasive, effective and safe procedure for patients with ureteral obstruction resulting from advanced malignant disease. As an alternative procedure to percutaneous nephrostomy, SNVB offers patients a better QoL.